Spatial and genetic structure of directly‐transmitted parasites reflects the distribution of their specific amphibian hosts. Issue 3 (18th January 2018) - Gustafson, Kyle D.; Newman, Robert A.; Rhen, Turk; Tkach, Vasyl V.
Abstract: Parasite distributions depend on the local environment in which host infection occurs, and the surrounding landscape over which hosts move and transport their parasites. Although host and landscape effects on parasite prevalence and spatial distribution are difficult to observe directly, estimation of such relationships is necessary for understanding the spread of infections and parasite–habitat associations. Although parasite distributions are necessarily nested within host distributions, direct environmental influences on local infection or parasite effects on host dispersal could lead to distinct landscape or habitat relationships relative to their hosts. Our aim was to determine parasite spatial structure across a contiguous prairie by statistical modeling of parasite–landscape relationships combined with analysis of population genetic structure. We sampled northern leopard frogs ( Lithobates pipiens ) and wood frogs ( L. sylvaticus ) for host‐specific lung nematodes ( Rhabdias ranae and R. bakeri ; respectively) across the Sheyenne National Grassland in southeastern North Dakota and developed primers for 13 microsatellite loci for Rhabdias . The two Rhabdias species exhibited different correlations with landscape characteristics that conformed with that of their hosts, indicating transmission is driven by host ecology, probably density, and not directly by the environment. There was evidence for localized, patchy spatial genetic structure, but no broader‐scale geographic patterns, indicating no barriers to host and parasite dispersal. Nematodes cohabitating in an individual frog were most genetically similar. Worms within the same wetland were also genetically similar, indicating localized transmission and resulting wetland‐scale patchiness are not completely obscured by broad‐scale host–parasite dispersal. Beyond individual wetlands, we found no evidence of genetic isolation‐by‐distance or patchiness at the landscape‐scale.